Hubungan Antara Hasil Belajar Matematika Dengan Hasil Belajar Fisika Di SMA Negri 6 Tangerang - Nita Risdianita (Concept: Journal of Social Humanities and Education, 2025)
This research aims to determine whether there is a relationship between mathematics learning outcomes and physics learning outcomes by taking the subject of exponent numbers in mathematics and the subject of temperature and heat in physics. This research was conducted on class X students at SMA Negeri 6 Tangerang in the second semester. The sample was taken at simple random (cluster sampling) by taking one class from nine existing classes with a total of 30 students. The method used is a survey method with correlation techniques. The independent variable in this research is the results of learning mathematics, while the dependent variable is the results of learning physics. Before the data is analyzed, the requirements test is first carried out, namely the normality test using the Lilliefors test and the regression significance test using analysis of variance (ANOVA). From the results of the normality test for the independent variable, it was obtained that L-count = 0,08770 < 0,161 = L-table, while for the dependent variable it was obtained that L-count = 0,1108 < 0,161 L-table, so it can be concluded that the two samples were normally distributed. The results of linear regression calculations are obtained The linearity test obtained F-count 1,067 < 2,45 = F-table so it can be concluded that the regression model is linear, meaning there is a linear relationship between the two variables. The regression significance test obtained F=count = 34,732 > 4,20 = F-table. This means that the regression model is significant. Hypothesis testing was carried out using product moment correlation analysis, then calculating the significance of the correlation using the student t-test. The results of the correlation coefficient calculation obtained r-count = 0,744 and the results of the t-student test calculation obtained t-count = 5,892, while the t-table value with a significance level of α=0,05 and degrees of freedom (dk) = 28 was 2,05. Because t-count = 5,892 < 2,05 = t-table means Ho is rejected. So the results of this research conclude that there is a relationship between mathematics learning outcomes and physics learning outcomes. The coefficient of determination (r2) was obtained at 0,554. This means that mathematics learning outcomes contribute 55,4% to physics learning outcomes.